2006
DOI: 10.1039/b602845d
|View full text |Cite
|
Sign up to set email alerts
|

Single DNA molecule stretching in sudden mixed shear and elongational microflows

Abstract: High-throughput stretching and monitoring of single DNA molecules in continuous elongational flow offers compelling advantages for biotechnology applications such as DNA mapping. However, the polymer dynamics in common microfluidic implementations are typically complicated by shear interactions. These effects were investigated by observation of fluorescently labeled 185 kb bacterial artificial chromosomes in sudden mixed shear and elongational microflows generated in funneled microfluidic channels. The extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 30 publications
3
124
0
Order By: Relevance
“…[23][24][25] In a broader context, similar disentanglement processes occur in polymers flowing over a polymer brush, 45 DNA separations using dilute neutral polymers as a sieving medium, 46 and flows of polymer solutions. 47 Finally, in direct linear analysis, 48,49 DNA collisions with posts may be a useful way of preconditioning DNA configurations before attempting to completely stretch DNA in an elongational flow [48][49][50] or electric field. 28,51 …”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In a broader context, similar disentanglement processes occur in polymers flowing over a polymer brush, 45 DNA separations using dilute neutral polymers as a sieving medium, 46 and flows of polymer solutions. 47 Finally, in direct linear analysis, 48,49 DNA collisions with posts may be a useful way of preconditioning DNA configurations before attempting to completely stretch DNA in an elongational flow [48][49][50] or electric field. 28,51 …”
Section: Discussionmentioning
confidence: 99%
“…The second half of this review discusses ways in which nanofluidic structures can be used to measure the mechanical properties of single DNA molecules [15][16][17][18] and perform sequence analysis. [19][20][21][22] As with the structures that are used to confine light, the devices that perform these tasks can be placed into one of two categories. They are either ''nanoslits,'' which allow a DNA strand to exist in a quasi two-dimensional (2D) plane, or they are called ''nanochannels'' and confine the polymer to a line.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of two straight channels of different widths connected by a hyperbolic contraction. The wide inlet channel has a width of w 1 = 200 m, and the outlet channel has a width of w 2 = 3.8 m. The shape of the hyperbolic contraction was chosen to create a uniform strain rate within the contraction 17,19 and has a length of ᐉ c =80 m. In front of the contraction are three rows of posts with each post having a 1 m radius. The posts are spaced 4 m center-to-center within each row, and the distance between rows is also 4 m center-to-center.…”
Section: Device Geometrymentioning
confidence: 99%
“…15,16 In DLA devices, the molecules are typically stretched by field gradients in microcontractions. 2,3,[17][18][19][20] However, in these strain-limited devices, molecular individualism 21 leads to a large population of molecules that do not reach full extension. Recent studies have shown that the effects of molecular individualism can be mitigated by "preconfiguring" the initial conformation of a molecule before it is stretched.…”
Section: Introductionmentioning
confidence: 99%